Detergent‐Like Polymerizable Monomers: Synthesis, Physicochemical, and Biochemical Characterization. Issue 33 (18th August 2020) - Bonnet, Christophe; Guillet, Pierre; Mahler, Florian; Igonet, Sébastien; Keller, Sandro; Jawhari, Anass; Durand, Grégory
Abstract : Three monomers with a maltose polar head, an alkyl hydrogenated chain, and an acrylamide‐based polymerizable moiety were synthesized. The self‐assembly properties in aqueous solutions of these monomers were studied by means of isothermal titration calorimetry (ITC), surface tension (SFT) measurements, and dynamic light scattering (DLS), which indicated the formation of small micellar aggregates of about 6 nm diameter. The critical micellar concentration (CMC) was found to depend on the length of the alkyl chain and on the nature of the polymerizable moiety, ranging from 0.35 mm to ca. 10 mm . The monomers were found to solubilize phospholipid vesicles and to extract a broad range of proteins from Escherichia coli membranes. Finally, the extraction of two membrane proteins, namely, the full‐length, wild‐type human G‐protein‐coupled receptor (GPCR) adenosine A2A receptor (A2A R) and the bacterial transporter AcrB was demonstrated. Abstract : Surfmers were synthesized and were found to be able to self‐assemble in water into micelles of ca. 6 nm in diameter at a critical micellar concentration that depends on the length of the alkyl chain. They were found to solubilize phospholipid vesicles and to extract a broad range of proteins from Escherichia coli membranes as well as the human adenosine receptor A2A R and the bacterial transporter AcrB.